2023
DOI: 10.1080/0142159x.2023.2192858
|View full text |Cite
|
Sign up to set email alerts
|

Sources of funding for research articles in medical education journals from 1999 to 2019

Abstract: Background: Prior studies report that most published medical education research is unfunded. We sought to determine the extent and sources of funding for medical education research articles published in leading journals, and how these have changed in the last two decades.Methods: All research articles published in Academic Medicine, Advances in Health Sciences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Among the 38 funded studies, six mentioned receiving funding from government entities and five from universities. Differently, a study analyzing 1822 articles found that governments and universities were the primary funding sources for medical education research published in high-impact scientific journals [ 84 ]. Exploring the role of these actors becomes important in promoting research on medical competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 38 funded studies, six mentioned receiving funding from government entities and five from universities. Differently, a study analyzing 1822 articles found that governments and universities were the primary funding sources for medical education research published in high-impact scientific journals [ 84 ]. Exploring the role of these actors becomes important in promoting research on medical competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors could have contributed to the recent improvement, such as increased funding for research, forthcoming supportive government policies, and the availability of educated and motivated researchers. 1 , 16 , 17 On the other hand, the COVID-19 pandemic might have played a role in the surge of medical research during the past period. Global medical journals have accelerated their publication process by almost 50%.…”
Section: Discussionmentioning
confidence: 99%